2021
DOI: 10.1039/d1nj03257g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced one-pot selective conversion of cellulose to ethylene glycol over NaZSM-5 supported metal catalysts

Abstract: The mesopores/micropores NaZSM-5 was synthesised by sol–gel method. The 5%Al–8%Ni–25%W/NaZSM-5 catalyst exhibited the highest cellulose conversion of 100% with EG yield as high as 89% (C mol%) at moderate reaction conditions which is highly applicable in polymer Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…The prepared catalysts were thoroughly characterized by various physico‐chemical methods. The results are discussed in detailed in our previous work for NaZSM‐5 supported metal catalyst [37] . Herein, we briefly discuss the catalyst characterization over HY and NaY supported metal catalyst.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The prepared catalysts were thoroughly characterized by various physico‐chemical methods. The results are discussed in detailed in our previous work for NaZSM‐5 supported metal catalyst [37] . Herein, we briefly discuss the catalyst characterization over HY and NaY supported metal catalyst.…”
Section: Resultsmentioning
confidence: 92%
“…The catalyst 5%Al‐ 8%Ni‐20%W loaded on different supports say NaY, HY, NaZSM‐5 and 5%Al‐ 8%Ni‐25%W HZSM‐5 yielded 50.1%, 62.8%, 69.5% and 67.7% of EG respectively at 220 °C, 70 bar H 2 pressure for 6 h reaction time for one‐pot cellulose conversion. Thus NaZSM‐5 was chosen to be the best support for further optimization studies and the results are reported in our previous publication [37] . It is understandable that the product selectivity and distributions are influence by the nature of the support.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] Recently, our group reported the selective production of ethylene glycol (EG), one of the most in-demand energy chemicals, from cellulose and glucose. 6,7 Like EG, 1,2-propanediol (1,2-PDO) is a glycol with a wide range of applications. Although used as an additive in cosmetics, nutritional products, medicines, and dyes, it is being increasingly used in anti-freeze and de-icing uids as well as a component of unsaturated polyester resins, liquid non-ionic detergents, and coolants.…”
Section: Introductionmentioning
confidence: 99%